1997
DOI: 10.1002/(sici)1099-1409(199707)1:3<227::aid-jpp17>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathia Macrocycle-bridged Dimeric with Hexakis (alkylthio) Substituents and Network Polymer Phthalocyanines

Abstract: 1,4,7,10-Tetrathia (12-crown-4)-bridged new polymeric phthalocyanines 9 and 10 have been synthesized by the reaction of tetracyanodibenzo[1,4,7,10-tetrathia (12-crown-4)] in the presence of a strong organic base or Zn ( OAc )2 respectively. Furthermore, 1,4,7,10-tetrathia (12-crown-4)-linked peripherally octa-substituted dimeric phthalocyanine 12, which contains a combination of hexakis(alkylthia) side chains was synthesized by the reaction of subphthalocyanine 11 with the iminois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The longer wavelength was encountered for the intense band compounds of 2e7. The UVeVIS spectra of the phthalocyanine polymers are very similar to those of crown ether [20], thia [21], oxa-thia [10], aza [22] substituted phthalocyanine polymers. The experimental UVeVIS bands of the phthalocyanine polymers were slightly different from theoretical values [27], and the results of mononuclear [7,8], binuclear [28], pentanuclear [29] and nono-nuclear [6] phthalocyanine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer wavelength was encountered for the intense band compounds of 2e7. The UVeVIS spectra of the phthalocyanine polymers are very similar to those of crown ether [20], thia [21], oxa-thia [10], aza [22] substituted phthalocyanine polymers. The experimental UVeVIS bands of the phthalocyanine polymers were slightly different from theoretical values [27], and the results of mononuclear [7,8], binuclear [28], pentanuclear [29] and nono-nuclear [6] phthalocyanine.…”
Section: Resultsmentioning
confidence: 99%
“…238e270 C and then extensive decompositions occurs at temperatures between 430 and 485 C. The initial decomposition temperatures of the compounds are in the order Zn O Cu O 2H O Ni O Co. No obvious correlation between the transition metal ions in the phthalocyanine rings is observed. The main decomposition temperatures of these phthalocyanine polymers are lower than crown ether [20], azamacrocycle [22] and alkylthio [21,25] substituted phthalocyanine polymers. The main purpose of the substitutions is to enhance the very limited solubility, and to enable the convenient preparation of a series of new phthalocyanine polymers.…”
Section: Resultsmentioning
confidence: 99%
“…In light of their unusual electrochemical and electronic properties, phthalocyanines (Pcs) are potentially useful additives. Pcs have attracted the attention of many researchers during the twentieth century and are still being actively studied in this century [ 18 19 ]. Many potential applications are expected for phthalocyanines (Pcs), which have high thermal and chemical stability, for instance as solar cell functional materials, gas sensors, and photodynamic therapy agents.…”
Section: Introductionmentioning
confidence: 99%
“…This report created a renewed interest in SubPcs, as it was shown that they could ring expand into unsymmetrical phthalocyanines. Several groups have recently synthesized SubPc derivatives, investigated their properties and explored their reactivity [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. This work has also grown to include a related class of compounds that contain an extended p-system.…”
Section: Introductionmentioning
confidence: 99%